Cerebrovascular Autoregulation-Based Optimal Mean Arterial Pressure During Prostate Surgery – A Secondary Analysis of a Prospective Cohort Study - Mewes C; Wei P; Yang Y; Kainz E; Kahl U; Beck S; Graefen M; Zöllner C; Fischer M (Therapeutics and Clinical Risk Management)
Caspar Mewes,1 Peipei Wei,1 Yi Yang,1 Elena Kainz,1 Ursula Kahl,1 Stefanie Beck,1 Markus Graefen,2 Christian Zöllner,1 Marlene Fischer1,3 1Department of Anesthesiology, University Medical Center Hamburg-Eppendorf, Hamburg, D-20251, Germany; 2Martini-Klinik, Prostate Cancer Center, University Medical Center Hamburg-Eppendorf, Hamburg, D-20251, Germany; 3Department of Intensive Care Medicine, University Medical Center Hamburg-Eppendorf, Hamburg, D-20251, GermanyCorrespondence: Marlene Fischer, Department of Intensive Care Medicine, University Medical Center-Hamburg-Eppendorf, Martinistrasse 52, Hamburg, 20246, Germany, Email mar.fischer@uke.dePurpose: Cerebrovascular autoregulation (CVA) is a homoeostatic regulatory function to maintain constant cerebral blood flow (CBF) despite changes in systemic blood pressure. The CVA-based optimal mean arterial pressure (MAPopt) refers to the MAP level at which the CVA mechanism reaches its lowest degree of pressure passiveness, allowing for optimal autoregulation. This study aimed to determine MAPopt by analyzing existing CVA data from patients undergoing non-cardiac surgery.Methods: This single-center investigation is a secondary analysis of prospectively recorded CVA data of patients undergoing oncologic prostate surgery. Intraoperative CVA was assessed using the cerebral oxygenation index (COx) derived from the simultaneous measurement of MAP and regional cerebral oxygen saturation (rSO2). Patient-specific MAPopt values were calculated using a second-order polynomial formula, in which the MAP related to the lowest COx was considered to be the intraoperative MAPopt.Results: A total of 180 patients were enrolled into the study. The average age was 63 years, 83.9% of patients had no or mild systemic disease. MAPopt determination was feasible in 128 patients, while 52 patients exhibited no U-shaped correlation between MAP and COx. The average intraoperative MAPopt was 81.7 mmHg ranging from 60.2 to 101.4 mmHg. The mean duration of intraoperative CVA measurement was 178 min.Conclusion: This study demonstrates a wide range of individual intraoperative MAPopt values and underscores that CVA-based MAPopt during non-cardiac surgery may differ from commonly accepted intraoperative MAP thresholds in clinical practice (ie 65 mmHg).Keywords: cerebral autoregulation, optimal mean arterial pressure, limits of cerebral autoregulation, non-cardiac surgery, personalized arterial pressure management